The effect of salinity stress on the morpho-physiology and protein profile of andrographis paniculata - Hossain, Md. Sanower (Kulliyyah of Science, International Islamic University Malaysia, 2016)
Medicinal plants are moving from fringe to mainstream use as they offer more effective and safer alternatives for diseases. Andrographis paniculata (Hempedu bumi) from the Acanthaceae family is one of the potential medicinal plants used traditionally to treat a wide range of ailments such as diabetes and hypertension since ancient time. This plant is cultivated in the field from seeds. However, growing the plant is challenging particularly in relatively high saline soils. Salinity stress is a prevalent abiotic stress limiting plant growth, development and productivity worldwide. Therefore, this study was conducted to determine the morphological, physiological and proteomic responses of A. paniculata to different concentrations of NaCl. The experiment was carried out using hydroponic systems based on completely randomized design and Hoagland solution was used as the nutrients source. The plants were subjected to 0, 20.55, 41.10, 66.75 and 92.40 mM of NaCl for 4 days. Salinity stress exhibited deleterious effects on the morphological appearance including dehydration, wilting, browning of leaves and shoots, narrow leaf lamina and leaf abscission. Generally, higher salt concentrations showed greater symptoms of salinity stress. Physiological traits such as plant height, leaf length and width, and root length were significantly reduced by salinity stress. Moisture content, relative growth rate and salt tolerance index were significantly reduced to 74.80%, -0.090 g/g/d and 57.90%, respectively at 92.40 mM NaCl treatment. Total protein contents of A. paniculata leaves in the higher concentrations of NaCl (41.10 mM) were significantly decreased. At the proteomic level, salt responsive proteome of A. paniculata were monitored using two-dimensional gel electrophoresis (2D-GE). A total of 18 proteins spots were changed significantly at p≤0.05. Fifteen differentially expressed proteins were identified, of which 6 proteins were up-regulated, 7 proteins were down-regulated and 2 proteins were absent in the salinity treatment. These proteins are triosephosphate isomerase, ferredoxin-NADP reductase, ribulose-1,5-bisphosphate carboxylase/oxygenase, D-ribulose-5-phosphate 3-epimerase, 2-Cys peroxiredoxin BAS1, 2-Cys peroxiredoxin BAS1-like protein, peroxidase 7, alkaline leaf peroxidase, NADP-dependent D-sorbitol-6-phosphate dehydrogenase, cleavage and polyadenylation specificity factor subunit 1 and hypothetical protein L484_018049. The proteins were mainly involved in photosynthesis, energy, carbohydrate and secondary metabolite metabolism, and plant stress and defence system. Knowledge on stress responsive proteins facilitates the understanding of molecular mechanisms of plants. The findings in this study expands our knowledge on salinity stress response in A. paniculata and may contribute to designing and developing salt tolerant plants in the future.